Architecture within a circular economy: Process mapping a resource-based design-bid-build project delivery system - Ali, Ahmed Kamal (Enquiry The ARCC Journal for Architectural Research, 2017)
In this paper, we develop a novel method for integrating system thinking into architectural design by mapping its processes in a standard process modeling language. We structured a decision-support framework using process mapping workflows to incorporate sustainable building materials and resource-based design decisions into the architectural practice. We turned to other disciplines’ knowledgebases, such as Business Information Technology (BIT), to develop a workflow for the Design-Bid-Build project delivery method (DBB). Mapping both current and the proposed design processes, including their activities, workflow, and decision nodes, was critical in defining roles, flow of information, and subsequent decisions. In this study, we utilized a qualitative methodology to capture the required knowledge from industry experts in resource-based design and then integrated our findings into a set of process maps to support the materials decisions by the architectural project team. This study establishes a system of information exchange to support the growth of the newly emerging industry of reuse stores and vendors. Through numerous interviews and knowledge capturing sessions with industry experts from the building material reuse industry that acknowledged an absence of a "system of information exchange." It is through this study that an overall system of information exchange will connect the links between the reuse industry and the AEC industry. The primary outcome of this study is a structured process for design with resource reuse. This process will redefine the DBB traditional design process by introducing new procedures, define information exchange and identify key decisions within the proposed processes, define responsibilities and identify key stakeholders. The author conducted an extensive multi-year knowledge capturing process with constructive feedback from the industry experts.